2005
DOI: 10.1160/th05-03-0146
|View full text |Cite
|
Sign up to set email alerts
|

The post-thrombotic syndrome: incidence and prognostic value of non-invasive venous examinations in a six-year follow-up study

Abstract: The ability to predict severity of the post-thrombotic syndrome (PTS) early after acute deep-vein thrombosis (DVT) is limited. The aim of our study was to examine the incidence of PTS prospectively and to evaluate the predictive value of non-invasive venous examinations shortly after DVT for the development of PTS. In 93 patients with DVT thrombosis score (TS), reflux, venous outflow resistance (VOR) and calf muscle pump dysfunction (CMP) were examined prospectively. After one, two and six years patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 26 publications
(23 reference statements)
6
100
2
4
Order By: Relevance
“…Previously we demonstrated that the measurement of TS, VOR and reflux at three months follow-up can be used as a proxy or surrogate endpoint for PTS [2]. In the current study there was no difference in the decline of VOR en TS between both groups.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Previously we demonstrated that the measurement of TS, VOR and reflux at three months follow-up can be used as a proxy or surrogate endpoint for PTS [2]. In the current study there was no difference in the decline of VOR en TS between both groups.…”
Section: Discussionsupporting
confidence: 45%
“…Although it was generally considered to take 5-10 years to develop PTS, the current opinion is that PTS already becomes clinically manifest within 1-2 years following the acute thrombotic event [1][2][3]. Impairment of quality of life is correlated with severity of PTS [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Dutch study 21 conducted in 2004 prospectively evaluated the incidence and severity of PTS in 93 DVT patients under careful clinical surveillance using the CEAP classification ( Figure 2). This study confirmed the findings from previous studies, whereby only half of DVT patients had no clear evidence of PTS (CEAP 0/1 and CEAP 2; Figure 2).…”
Section: Clinical Features Of Ptsmentioning
confidence: 99%
“…Acute iliofemoral deep vein thrombosis (DVT) is a major cause for morbidity, as approximately half of the patients managed conservatively with anticoagulation therapy and compression stockings develop the post-thrombotic syndrome (PTS) [1][2][3][4]. The residual thrombus load correlates with the probability of a future PTS [5,6].…”
Section: Introductionmentioning
confidence: 99%